Úma análise comparativa entre o Procedimento de Manifestação de Interesse (PMI) e o diálogo competitivo - Lima, Cláudia Castello Branco (2014)
This study aims at analyzing the main aspects of the General Law on Public Tenders (Federal Law nr. 8666/1993) and comparing these with contemporary forms of pre-contractual relations: the declarations of interest on the part of private enterprise, the experience of the State of Minas Gerais and competitive dialogues, the experiences of the European Union and of the United States. To this purpose, in a first phase, the main changes occurred since 1993 in the tendering processes are discussed, such as the creation of the Public-Private Partnerships (PPPs) and the Differentiated Contracting Regime (RDC, in the Portuguese acronym). In sequence, a comparison between the main alterations implemented. Finally, summarizing conclusions regarding the comparison between the Declaration of Interest Procedure (PMI) and the Competitive Dialogue, which may lead to perfecting public tenders.